RETRACTED: Epidemiology as a prophilactic discipline in contemporary medicine (In honour of the 80-th Anniversary of the chair of epidemiology and evidence-based medicine of the First MGMU named after I. M. Sechenov) - N. I. Briko; V. I. Pokrovsky; A. Ya. Mindlina (Сеченовский вестник)
RETRACTED ARTICLEThis article deals with the actual problems of contemporary epidemiology.